Corrigendum: Metabolic Profiling of a CB2 Agonist, AM9338, Using LC-MS and Microcoil-NMR: Identification of a Novel Dihydroxy Adamantyl Metabolite - Honrao, Chandrashekhar; Ma, Xiaoyu; Kulkarni, Shashank; Joshi, Vinit; Malamas, Michael; Zvonok, Alexander; Wood, JodiAnne; Kautz, Roger A.; Strand, David; Guo, Jason J.; Makriyannis, Alexandros (Frontiers in pharmacology, 2021)
[This corrects the article DOI: 10.3389/fphar.2020.575691.].